2011
DOI: 10.1007/s11270-011-0817-6
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Modeling of Denitrification in Soils with Natural and Depleted Organic Matter

Abstract: Nitrogen fertilizers used in agriculture often cause nitrate leaching towards shallow groundwater, especially in lowland areas where the flat topography minimize the surface run off. In order to introduce good agricultural practices that reduce the amount of nitrate entering the groundwater system, it is important to quantify the kinetic control on nitrate attenuation capacity. With this aim, a series of anaerobic batch experiments, consisting of loamy soils and nitrate-contaminated groundwater, were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Nitrite accumulates in our experiment for both heterotrophic and autolithotrophic denitrification, a phenomenon, which has been observed in a multitude of studies (e.g., Bosch et al, ; Carrey et al, ; Mastrocicco et al, ; Parmentier et al, ). It was observed that the rates for nitrate and nitrite reduction are affected differently by specific environmental conditions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nitrite accumulates in our experiment for both heterotrophic and autolithotrophic denitrification, a phenomenon, which has been observed in a multitude of studies (e.g., Bosch et al, ; Carrey et al, ; Mastrocicco et al, ; Parmentier et al, ). It was observed that the rates for nitrate and nitrite reduction are affected differently by specific environmental conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Some of those models do not consider in detail microbial growth (Antoniou et al, 2013;Engelhardt et al, 2014), while others account for microbial growth and decay (Clement et al, 1997;Rodríguez-Escales et al, 2016). Some investigations are based on laboratory studies (Clement et al, 1997;Mastrocicco et al, 2011;Molins et al, 2015;Rodríguez-Escales et al, 2016), while others analyze field investigations (Engelhardt et al, 2014;Lee et al, 2009). A special case is the thermodynamic approach which was employed by André et al (2011) for their laboratory studies using thermodynamic factors similar to Monod factors and which account for changes in the thermodynamic equilibrium of the redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…According to the origin and texture of the soil matrix, organic matter content varies from <2% for silty loam to 28% for peat [33]. The shallow unconfined aquifer, whose thickness ranges between 2 and 7 m, is fed by rain infiltration and the surface water system; thus, the water table is usually very proximal to the ground surface [34]. Agriculture is the dominant land use with ~80% of the watershed area classified as utilized agricultural land (UAA).…”
Section: Study Areamentioning
confidence: 99%
“…Reaction 2 is the overall reaction that merges intermediate reactions involving N2O (Table S2). These overall reactions have been used widely for mass and electron balance in modeling nitrate bioreduction in wastewater treatment engineering and agricultural systems (Ahn, 2006;Mastrocicco et al, 2011;Matějů et al, 1992;McCarty et al, 1969;Rittmann and McCarty, 2001;U.S. EPA, 1993).…”
Section: Mathematical Interpretation Of Observationsmentioning
confidence: 99%